Distinct isolates of uropathogenic Escherichia coli differentially affect human sperm parameters in vitro. (30th September 2013) - Boguen, R.; Uribe, P.; Treulen, F.; Villegas, J. V.
Summary Sperm motility and vitality are decreased in male genital tract infection. Uropathogenic Escherichia coli (UPEC) are frequently associated with sperm parameter loss, but there are no reports to date regarding the effects of different E. coli isolates on human spermatozoa. The aim of this work was to compare the effect in vitro of different E. coli isolates on human sperm parameters. Normal spermatozoa were incubated with E. coli isolated from nine men with urinary tract infection. After 1 h of incubation, sperm motility, vitality and mitochondrial membrane potential (ΔΨm) were measured. The E. coli isolates were serotyped with specific antisera. Sperm motility was decreased with five of nine E. coli isolates. Two UPEC were typed as O6 strains, and they did not decrease sperm motility in the same experimental conditions as the other five isolates, despite the described high pathogenicity of the O6 strain in urogenital infections. Neither UPEC analysed affected vitality or ΔΨm. UPEC isolates were shown to be heterogeneous in their effects, suggesting the need to characterise the pattern defining the pathogenicity of E. coli on human spermatozoa.